2008
DOI: 10.1303/aez.2008.563
|View full text |Cite
|
Sign up to set email alerts
|

A novel gene associated with intraspecific predation in Spodoptera litura larvae

Abstract: We investigated the inheritance of cannibalistic behavior in larvae of the common cutworm, Spodoptera litura. The fact that artificial selection of non-cannibalistic animals over 17 generations resulted in decrease of their cannibalistic behavior is clearly the proof of their inheritance of this behavior. Average frequency of cannibalism in selected larvae (3.2%) was significantly lower than that in non-selected larvae (24.5%). We employed the differential display RT-PCR analysis to evaluate differences in gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…In highly gregarious locusts and crickets cannibalism is an important source of protein and salts, which allows the cannibals to survive longer and migrate farther; cannibalism avoidance is an important factor driving their mass migrations 5,7 . The rapid response to artificial selection for reduced incidence of intraspecific predation in Spodoptera caterpillars 23 demonstrates that it is a heritable trait with substantial genetic variation. Although its benefits are unclear, cannibalism in Spodoptera carries a cost in terms of disease transmission 24 .…”
mentioning
confidence: 99%
“…In highly gregarious locusts and crickets cannibalism is an important source of protein and salts, which allows the cannibals to survive longer and migrate farther; cannibalism avoidance is an important factor driving their mass migrations 5,7 . The rapid response to artificial selection for reduced incidence of intraspecific predation in Spodoptera caterpillars 23 demonstrates that it is a heritable trait with substantial genetic variation. Although its benefits are unclear, cannibalism in Spodoptera carries a cost in terms of disease transmission 24 .…”
mentioning
confidence: 99%
“…For example, sibling cannibalism, i.e., the feeding of unhatched male eggs by hatched female larvae, increases the fitness of surviving larvae in some insect species harboring male killers ( 9 ). Although there are no records of S. litura larvae feeding on eggs, it is apparent that cannibalism between larvae occurs ( 41 ). This suggests that egg consumption probably occurs and contributes to the fitness of SlMKV-infected S. litura females.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported that non motile (egg and pupae) or less motile stages (younger larvae) are more prone to cannibalism by older larvae and more on natural host when compare to artificial diet in mass rearing. Ryuda et al (2008), favored to rear larvae separately on artificial diet to avoid cannibalism in tobacco cutworm. Separate or singly rearing on artificial diet in vials, is a good option to avoid cannibalism in laboratory rearing.…”
Section: Resultsmentioning
confidence: 99%